Redefining animal mortality accounting within indigenous paradigms and sustainability frameworks - Mustafa, Hasri (2025)
This paper explores how concepts of animal sustainability and institutional responsibility are reshaped through the documentation of animal mortality at Zoo Negara Malaysia. While global concern for animal welfare and conservation has intensified, scholarly attention has seldom examined how sustainability principles are operationalised within zoo management systems, especially through an indigenous and ecological lens. This study bridges that gap with a multidisciplinary analysis of Zoo Negara’s historical mortality records, institutional documents, and conservation practices, critically engaging with indigenous critiques of Western conservation models (Todd, 2014, 2016, 2018, 2022). It unfolds along two interrelated trajectories: first, examining how Zoo Negara’s practices around documenting and disclosing animal fatalities serve as instruments of transparency and ethical accountability; and second, critically analysing how current biological asset accounting standards both reveal and conceal the complex realities of zoo-based conservation and breeding efforts. Findings highlight persistent tensions in conventional accounting classifications, including challenges in selecting appropriate measurement units across diverse species, valuing animals amid fluctuating care costs, and accounting for reproductive outcomes. Framed through indigenous paradigms that challenge the commodification of animal life and emphasise relationality, alongside ecological models that foreground biophysical realities over financial abstractions, the study proposes alternative, holistic approaches to mortality accounting. These approaches prioritise relational accountability to animal kin while integrating sustainability metrics that respect ecological interconnectedness. In doing so, this research offers Zoo Negara and similar institutions pathways to reconceive how they account for life and death, honouring indigenous wisdom, ecological integrity, and ethical stewardship, within a redefined sustainability framework.